МУЗЕЙНЫЕ КОЛЛЕКЦИИ – ИНФОРМАЦИОННЫЙ ПОТЕНЦИАЛ ИСТОРИЧЕСКОЙ НАУКИ - Досмаганбетов, С.; Сейилбекова, Р. (SCIENCE and SOCIETY, 2021)
This article deals with the potentiality of the museum works and museum collections to the historical sciences on their informativity, the history of the formation of state history and culture museum of the Republic of Karakalpakstan and the valuable museum collections. Moreover, this article focuses on the matters in recent years on the degree of state politics like saving the valuable historical and cultural riches of our country.
Keywords: museum; archaeological sites; ethnography; anthropology; cultural studies